Applications of food color and bio-preservatives in the food and its effect on the human health. (October 2022) - Dey, Subhashish; Nagababu, Bommu Hema
Highlights: Color is a key component to increase the ultimate appetizing value and consumer acceptance. Synthetic food colors have been more used than the natural food colors due to their low cost, and easy available. The uses of synthetic food colors may lead to the severe health problems. The food colors must be added in food at certain concentration and within the acceptable limit. Abstract: Color is a key component to increase the ultimate appetizing value and consumer acceptance towards foods and beverages. Synthetic food colors have been increasingly used than natural food colors by food manufacturers to attain certain properties such as low cost, improved appearance, high color intensity, more color stability and uniformity. Varied foods and beverages available in the market may contain some non-permitted synthetic colors and over use of permitted synthetic colors. This may lead to severe health problems such as mutations, cancers, reduced hemoglobin concentrations and allergic reactions. Moreover, 60% of the beverages violated the label requirement without including proper color ingredients. The study concluded that there is a high tendency to use synthetic food colors in confectioneries and beverages and some confectioneries contain unidentified colors including a textile dye. Therefore, the implementation of regulations and awareness programs of food colors for consumers and food manufacturers are highly recommended.